Alih Kode dalam Tuturan Penjual dan Pembeli di Pasar Pusat Jalan Hos Cokroaminoto Kelurahan Sukaramai Kota Pekanbaru - Yosi Darmayanti; Erni (UIR PRESS, 2021)
As social beings, humans need tools in the form of language in interacting and socializing. The diversity of regional languages scattered throughout Indonesia is a general description of the wealth of the Indonesian people, which has a personality and elegance in its different variations. Code switching events can also occur in the form of oral and written communication. In oral communication, code switching events are usually carried out consciously by the speaker, whereas in written communication, code switching events are usually carried out with the life experience of an author. Code switching is a transition event from one code to another. If a speaker initially uses code A (for example Indonesian) and then switches to using code B (for example Javanese). This study examines two problems, namely (1) what are the types of code switching in the speeches of sellers and buyers in the Central market of Jalan Hos Cokroaminoto, Sukaramai Village, Pekanbaru City? and (2) what are the factors that cause code switching in the speeches of sellers and buyers at the Central market of Jalan Hos Cokroaminoto, Sukaramai Village, Pekanbaru City ?. The theory used in this research is the code switching theory put forward by Abdul Chaer and Leoni Agustina (2010) and Kunjana Rahardi (2010). The research approach that the author uses is a qualitative approach. The method used in this research is the content analysis method. Form the data that the authors obtained during the research conducted at the central market Jalan Hos Cokroaminoto Kelurahan Sukarama Pekanbaru city none of the external code switching data was found, all speeches between thr seller and the buyer are only contained in the internal code transfer, namely form Indonesian into Minang, Minang into Indonesian,Indonesian into javanese, javanese into Indonesian, Indonesian into Malay, and Malay into Indonesian. (2) factors that cause code switching in the speech of sellers and buyers at the Central market Jalan Hos Cokroaminoto Village Sukaramai City Pekanbaru has 8 the details are as follows : (a) the seller's annoyance to the buyer, (b) the buyer’s annoyance to the buyer to the seller, (c) the buyer has a hidden purpose, (d) the seller wants to match the code used by the buyer, (e) expression of surprise on the part of the buyer, (f) the presence of other potential buyers during the conversation, (g) the seller wants to pretend with the buyer (does not exist), and (h) the seller wants to joke with the buyer. These factors are dominated by the seller wants to match the code used by the buyer.